Desulphurizing Pig Iron By Ladle Treatment With Soda Ash Or Caustic Soda, And A Nontechnical Discussion Of The Reactions Of Alkali Slags - George S. Evans (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1938)
CERTAIN American operators believe that desulphurizing in the ladle offers a means of increasing blast-furnace and open-hearth yields with the possibility of improvements in quality of the steel. In fact, several producers have experimented with practically all of the known desulphurizing agents, including both standard grades of the alkalies and special preparations that have been offered from time to time during the past several years. Some of these are regularly being used today in large-scale commercial operations, with good results. Also, it is the practice to treat off-sulphur casts in the blast-furnace ladle at a number of plants. It is not known, however, that anyone in the steel industry (American) has ever adequately equipped a plant for desulphurizing blast-furnace metal in an efficient manner as regular operating practice. The purpose of this paper is to illustrate the importance of correct equipment and proper handling for obtaining uniform and efficient results. As will be shown, at the temperature of molten iron the alkalies are instantly neutralized by any free slag present, dissipating their desulphurizing value. Entrained silicates are rapidly washed out of the metal bath by the highly basic soda slags and will be satisfied ahead of desulphurizing reactions with FeS. More or less of the reagent will always be used up through reactions with the refractory lining. Desulphurization will be limited to the action of the free alkali then remaining in the slag. Causes for the erratic results generally found with desulphurizing tests in blast-furnace transfer ladles would include, among other things, variations in the quantity of furnace slag coming down with the metal, and differences in the percentage of kish and entrained silicates in the different casts. As the alkalies instantly unite with any free slags or silicates present, these, with any kish coming off, both dilute the reagent and reduce the surface contact between the slag and metal, thereby retarding the desulphurizing reactions.